Collaborative Networks in the Internet of Services 13th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2012, Bournemouth, UK, October 1-3, 2012. Proceedings - Camarinha-Matos, Luis M.; Xu, Lai.; Afsarmanesh, Hamideh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 13th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2012, held in Bournemouth, UK, in October 2012. The 61 revised papers presented were carefully selected from numerous submissions. They provide a comprehensive overview of identified challenges and recent advances in various collaborative network (CN) domains and their applications with a particular focus on the Internet of Services. The papers are organized in topical sections on service enhanced products; service composition; collaborative ecosystems; platform requirements; cloud-based support; colllaborative business frameworks; service design; e-governance; collaboration in traditional sectors; collaboration motivators; virtual organization breeding environments; collaboration spaces; designing collaborative networks; cost, benefits and performance; identification of patterns; co-innovation and competitiveness; collaborative behavior models; and risks, governance, trust.
Service Enhanced Products -- Service Composition -- Collaborative Ecosystems -- Platform Requirements -- Cloud-Based Support -- Collaborative Business Frameworks -- Services Design -- e-Governance -- Collaboration in Traditional Sectors -- Collaboration Motivators -- Virtual Organization Breeding Environments -- Collaboration Spaces -- Designing Collaborative Networks -- Cost, Benefits and Performance -- Identification of Patterns -- Co-innovation and Competitiveness -- Collaborative Behavior Models -- Risk, Governance, Trust.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Information Systems; Management information systems; Computer Science; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Computer Communication Networks; Software Engineering; Management of Computing and Information Systems; Business Information Systems